Seed Production of Goldenmane Tickseed - Jeffrey G. Norcini (EDIS)
The genus Coreopsis is Florida's State Wildflower. Coreopsis basalis, commonly known as Goldenmane Tickseed or Dye Flower, brightens roadsides and fields of central and north Florida from as early as April to as late as mid-June. During dry years, however, flowering is mainly in May. This drought-tolerant, annual usually is found from North Carolina to Texas, although it has been observed as far north as Connecticut and Illinois. This document is ENH 882, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date November 2003.